Judaism in late antiquity. - Neusner, Jacob, 1932-; Avery-Peck, Alan J. 1953-; Chilton, Bruce. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2001)
The authors have asked of the documents of the Dead Sea Library found at Qumran a simple question: how does each participate in a single Judaic religious system? They propose a reading of the Scrolls from the hypothesis that all of them, in one way or another, rest upon one, authoritative, Judaism. Their analysis of the Dead Sea Scrolls describes how diverse writings hold together to make a single coherent statement, to stand for a religious system possessed of integrity and wisdom. This account of the world view of Judaism covers principal questions addressed to any Judaic religious system: the doctrine of God, the Torah, and matters of history, wisdom, and mysticism. When it comes to the way of life, they include the evidence of the material culture of the community as well as practical matters of religious conduct. How the community's world view comes to realization is suggested by its treatment of the calendar, by its provision of laws that concern women, by questions of cultic and secular purity, by its piety and forms of worship and views of Temple, sacrifice, and the like. Finally, with the community's definition of 'Israel' and of itself in relationship to 'Israel', inclusive of Israelites excluded from this 'Israel', an account is gained of the theory of who and what is Israel that animates the particular Judaism represented in these writings.